Modifikasi Solar Water Destiler Dengan Menambahkan Unit Pemanas Berenergi Solar Cell - Iskandar Zulkarnain; Kelik Istanto (Jurusan Teknologi Pertanian, 2020)
Increasing the heat energy in the evaporator box from the Water Solar Destiler, by adding a wire heater aims to increase the heat energy in the evaporator box so that it will speed up the evaporation process in the evaporator box. The more liquid that is broken down due to heat energy into water vapor, the more discharge will be produced. Based on the results of the observations made, the addition of a wire heater in the evaporator city with AC electricity generated by solar panels, increased the purified water by 248.78%, from 1745 ml to 4341 ml, with the thickness of the water being purified as thick as 1 cm which was dried in the sun. for 10 hours starting from 07.00 WIB to 17.00 WIB.